2019
DOI: 10.37358/rc.19.9.7538
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates from Endotracheal Aspirates and their Antimicrobial Resistance Pattern in Patients from Intensive Care Unit

Abstract: The emergence of multidrug-resistant (MDR) pathogens, especially for intensive care unit (ICU) patients is a serious threat to public health. To determine the frequency and antibiotic resistance pattern of bacterial pathogens isolated from tracheal aspirates of the patients admitted in ICU. The retrospective study included endotracheal aspirates from 734 patients admitted to the ICU, from January to December 2017. The analysis of the resistance patterns for the action of the appropriate antibiotics was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…In other studies conducted with the aim of highlighting the MDR strains which caused other types of infections besides BSI, Klebsiella ranks first among isolated microorganisms, 12 , 14 , 15 with the same findings in other researchers’ studies. 16 …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In other studies conducted with the aim of highlighting the MDR strains which caused other types of infections besides BSI, Klebsiella ranks first among isolated microorganisms, 12 , 14 , 15 with the same findings in other researchers’ studies. 16 …”
Section: Discussionsupporting
confidence: 73%
“…In our research, both Coagulase-negative Staphylococci (CoNS) and MRSA showed high resistance to penicillin and fluoroquinolones, which is similar to other studies. 12 , 14 , 15 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…isolates revealed a very high level of resistance against third-generation cephalosporins (over 95%), carbapenems (around 90%), piperacillin-tazobactam (around 90%), fluoroquinolones (around 90%), and aminoglycosides (around 85%). These findings are consistent with those from other studies [28][29][30][31] and with data on antibiotic consumption and antibiotic resistance in Romania, showing an increasing extended resistance (for A. baumannii, carbapenem resistance was 93.6% and multi-resistance was 89.4%, occupying third place for both indicators among EARS Net states) [15]. A significantly increasing trend was also observed in the antimicrobial resistance rate against colistin (p < 0.001), which is an issue of great concern because colistin remains one of the very few antibiotics which are consistently active against these bacterial species.…”
Section: Discussionsupporting
confidence: 93%
“…S. aureus colonizes a wide variety of tissues, which can either result in less-severe manifestations such as folliculitis, or in potentially fatal infections like pneumonia, endocarditis, osteomyelitis, and sepsis [6,7]. The pathogen is known to cause recurring diseases, indicating that humans do not naturally develop a strong, long-lasting immune response against it [6].…”
Section: Introductionmentioning
confidence: 99%